ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA CREDIT UNION DI DESA SOSOK, KECAMATAN TAYAN HULU - B01111094, Anna Utami Danilia Prasiwi (Jurnal Pembangunan dan Pemerataan, 2015)
The title of this research is the analysis of the factors affecting net income figure in Credit Union at Sosok of Tayan Hulu Subdistrict. This study aims to identify and analyze the factors that influence the rest of the results of operations in Credit Union at Sosok of Tayan Hulu Subdistrict.This research uses descriptive method with quantitative approach using multiple linear regression model, the classic assumption test, as well as statistical analysis tools that is test of determination (R2), F test and t test to test the hypothesis of whether the number of members, the number of vehicle loans and venture capital, and number of loss vecile loan and loss venture capital effect towards net income. The data used in this research is panel data with secondary data obtained from four Credit Unions located at Sosok Tayan Hulu Subdistrict in 2010-2014. The analysis using SPSS 20 program in the data processing. The results showed that the number of members influence positively and significantly to 4,311, while the number of vehicle loans and venture capital negatively and significantly effect of -2.572 and the amount of bad loans and venture capital vehicle positively and significantly effect of 3.086. The coefficient of determination (R2) of 0.722, which means the amount of influence exerted by a variable number of members, the number of vehicle loans and venture capital and the amount of bad loans and venture capital vehicles to 72.2% while the remaining 27.8% is influenced by other factors Keywords: Number of Members, Total Loans Vehicles & Venture Capital, Total Loss Vehicle Loans & Venture Capital and Net Income